PKM HORISON HARAPAN BUMDESA “JATIDIRI” MELALUI UNIT USAHA BERBASIS KERAJINAN DAN SENI BUDAYA DI DESA JATIGUWI SUMBERPUCUNG MALANG - Dhanny Septimawan Sutopo; Arief B. Nugroho; Anif Fatma Chawa (Jurnal Abdimas Bina Bangsa, 2023)
Jatiguwi Village is a rural area located in Sumberpucung District, Malang Regency, East Java Province and is located about 35 km to the southwest of Malang City. The opportunity for economic development in Jatiguwi Village has begun to be promoted through Village-Owned Enterprises (BUM Desa). In this village, BUMDesa has been formed since 2016 under the name of "Jatidiri" BUMDesa which already has several business units, looking at the potential of Wayang Topeng Malangan cultural art which is a typical asset of Jatiguwi Village, so since 2021 the end has been trying to be developed in an effort to raise "Jatidiri" BUMDesa. The consideration of the development of this new business unit is not without reason, because it considers the elements of economic potential that exist in this cultural art. However, the lack of human resources capacity in BUMDesa to carry out business development. As well as other obstacles, namely the lack of knowledge of marketing strategies for BUMDesa products so that they are less able to compete and penetrate the market. So through this Community Service activity, it is sought to be completed, so that in the future through the strong institutional role of the "Jatidiri" BUMDesa will be able to perform and can make a real contribution to efforts to improve the welfare of the lives of the residents of Jatiguwi Village with open business opportunities and be able to increase Village Original Income